2001
DOI: 10.1121/1.4744338
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of techniques for reducing flow-induced cavity resonance

Abstract: Excitation of cavity resonance by flow over an aperture is often a source of unwanted noise in aerospace, automotive, and marine applications. An experimental investigation of three resonance reduction techniques was conducted. These were: a fence at the upstream edge, fluid injection, and a new technique developed by the author, in which fluid from the boundary layer is diverted into the cavity. Spectra of the pressure in the cavity were obtained for various flow speeds. Results show that the fence and the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The convection velocity is normalized by the free-stream velocity, and x is normalized by the overall length of the opening. The unobstructed condition is essentially a baseline, and is similar to the results reported in Zoccola (2000), who showed that for flow over an unaltered opening, the vortex decelerates as it approaches the downstream edge. For the 17 m/s condition, the convection velocity in the upstream half of the opening shows essentially the same behavior as the baseline condition.…”
Section: Article In Presssupporting
confidence: 82%
See 3 more Smart Citations
“…The convection velocity is normalized by the free-stream velocity, and x is normalized by the overall length of the opening. The unobstructed condition is essentially a baseline, and is similar to the results reported in Zoccola (2000), who showed that for flow over an unaltered opening, the vortex decelerates as it approaches the downstream edge. For the 17 m/s condition, the convection velocity in the upstream half of the opening shows essentially the same behavior as the baseline condition.…”
Section: Article In Presssupporting
confidence: 82%
“…The results show a region of positive energy production (source) near the downstream edge and a region of negative energy production (sink) in the upstream half of the opening. Reasonably good agreement with this result was found by Zoccola (2000), who reported measurements of the energy production term distribution for conventional cavity opening which showed regions of positive and negative energy production in the opening, with the positive being of greater magnitude and positioned above and somewhat downstream from the negative region. Essentially the same distribution was observed for measurements on configuration S0a at 14 m/s.…”
Section: Energy Productionsupporting
confidence: 80%
See 2 more Smart Citations